Professional training of specialists of economic sectors in Poland and Ukraine: comparison criteria - Zagorodnya Alla (Borys Grinchenko Kyiv Metropolitan University, 2015)
The author reveals the criteria for comparison of professional training in the field of economic higher education institutions of the Republic of Poland and Ukraine. The author argues that the problem of professional training of the economic sector in higher education is complex and requires coordination of efforts of various courses and disciplines, to form an idea of the phenomenon of system performance, conditions, criteria and factors of its increase, methods of measurement. The author defines performance criteria as measurements or benchmarks used to assess achievement of efficiency standards. Performance as quality indicators, performance or value standard for evaluating the effectiveness of the student show how well students meet expectations of what they should know and be able to do that is expressed in levels or points. The analysis by research indicates the following performance criteria for the evaluation of the functioning of training: operating relating to the organization and flow of basic processes and patterns and express their development; economic, related to the size (value) of positive and negative effects (runs); Information related to the organization and how the system processes the information, expressing the impact of these processes on the system behavior; safety-related elements readily system, particularly technical means to express the impact of technology on the behavior of the system; performance related to the functioning of credit. Keywords: economic education; concept of study; education; comparative education; professional training.